Wage Subsidies and Hiring Chances for the Disabled: Some Causal Evidence - Stijn Baert (Institute for the Study of Labor (IZA), 2014)
We evaluate the effectiveness of wage subsidies as a policy instrument to integrate disabled individuals into the labour market. To identify causal effects, we conduct a large-scale field experiment in Belgium. Our results show that the likelihood of a disabled candidate receiving a positive response to a job application is not positively influenced by revealing entitlement to the Flemish Supporting Subsidy.
Keywords: I38; J14; J78; 330; labour market policy evaluation; wage subsidies; disability; discrimination